2019
DOI: 10.1057/s41599-019-0279-9
|View full text |Cite|
|
Sign up to set email alerts
|

Fake news game confers psychological resistance against online misinformation

Abstract: The spread of online misinformation poses serious challenges to societies worldwide. In a novel attempt to address this issue, we designed a psychological intervention in the form of an online browser game. In the game, players take on the role of a fake news producer and learn to master six documented techniques commonly used in the production of misinformation: polarisation, invoking emotions, spreading conspiracy theories, trolling people online, deflecting blame, and impersonating fake accounts. The game d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
432
5
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 423 publications
(527 citation statements)
references
References 61 publications
28
432
5
8
Order By: Relevance
“…The fake news game Bad News is a real-world inoculation intervention (https://www. getbadnews.com) used by schools and governments that finds that pre-emptively exposing people to small doses of misinformation techniques (including scenarios about COVID-19) can reduce susceptibility to fake news 131,132 and could be embedded directly on social media platforms 133 .…”
Section: Conspiracy Theoriesmentioning
confidence: 99%
“…The fake news game Bad News is a real-world inoculation intervention (https://www. getbadnews.com) used by schools and governments that finds that pre-emptively exposing people to small doses of misinformation techniques (including scenarios about COVID-19) can reduce susceptibility to fake news 131,132 and could be embedded directly on social media platforms 133 .…”
Section: Conspiracy Theoriesmentioning
confidence: 99%
“…2) Modification of agent reinfection rate: This strategy controls the network behavior by selecting one or more agents for treatment to decrease its reinfection rate. In the epidemiological setting, this is vaccination, and in the behavioral setting, it could be inoculation as in psychology research [2]. We make just one modification to the example network of four agents: β 42 = 1 becomesβ 42 = 0.3.…”
Section: A Control From Endemic To Infection-free Steady Statementioning
confidence: 99%
“…For example, in psychology there is a well-established "inoculation theory" [2], [20], [21], which has shown that an effective way to combat the spread of misinformation is to preexpose people to misinformation so that they develop at least partial cognitive immunity to subsequent contact with misinformation. Examples also abound in social animal behavior.…”
mentioning
confidence: 99%
“…Inoculation differs from debunking strategies, which refute false claims only after they have been seen or heard; it is thus especially valuable, since disinformation is often resistant to debunking after the fact Lewandowsky et al, 2012). Furthermore, unlike topic-specific debunking, inoculation aims to instill recipients' domain-general competence to see through attempts of manipulation (Roozenbeek & van der Linden, 2019), making it a particularly suitable cognitive strategy when fact-checking or evidence-based refutation is costly or unavailable.…”
Section: Inoculation: Boosting Cognitive Resilience To Misinformationmentioning
confidence: 99%